Respiratory Morbidity and Mortality of Traumatic Cervical Spinal Injury - Pokhrel, Nabin; Neupane, Aastha; Thapa, Nabin; Yadav, Rupesh Kumar; Hamal, Pawan Kumar; Malla, Pragya (Journal of Nepal Health Research Council, 2024)
Background: Traumatic cervical spinal injuries can severely affect respiratory function and cause significant morbidity and mortality. The typical respiratory morbidity in cervical spine injury is Atelectasis, Ventilator-associated pneumonia, acute respiratory distress syndrome and delayed weaning, etc. The study aims to see the prevalence of respiratory morbidity as well as mortality associated with cervical spine injury. Methods: Cross sectional study based on retrospective data was conducted on the X Sciences with the existing hospital record during the period of 3 years to find out the prevalence respiratory morbidity like Ventilatory Associated Pneumonia, delayed weaning, ARDS, atelectasis of traumatic cervical spine injury, determine the prevalence, type, and impact of respiratory morbidity and mortality in this population. Results: Total no 76 patients data meeting the inclusion criteria included in study. Male patients were more prone to develop traumatic cervical spinal injuries (SCI). The prevalence of respiratory morbidity in term of VAP(57.89), delayed weaning(46.05) and Atelectasis(22.36) was high. Patients with Asia A Neurology has higher association for VAP and delayed weaning, while Asia E Neurology patients had no respiratory morbidity. The study found a significant positive association between respiratory morbidity with hospital stay, and ventilator days (p-value: 0.019 and 0.048). A total of 15 patients died, 28.95% were discharged on request and 40.8% leaving the hospital against medical advice. Conclusions: The prevalence of respiratory morbidity higher in cervical spine injury. Furthermore, it has associated with prolonged ICU and ventilator days and increase in mortality. Keywords: ARDS; atelectasis; delayed weaning; respiratory morbidity; traumatic SCI.